The Integration of Internet of Things (IoT) in Smart Cities A Systemic Approach to Urban Management - Umar, Genius; Adria (Journal Informatic, Education and Management (JIEM), 2024)
The use of the Internet of Things (IoT) has become an integral part of efforts to develop efficient and sustainable smart cities. This research aims to investigate the integration of IoT in the context of systemic urban management. The research methods employed include in-depth literature studies, comprehensive policy document analysis, and field research to understand IoT implementation in several smart cities. The results indicate that a systemic approach to integrating IoT in urban management is crucial to achieving efficiency and sustainability. This integration involves various aspects, including physical infrastructure, information systems, policies, and community participation. In this context, the research highlights the importance of developing integrated and interoperable IoT infrastructure, open data platforms, and adequate regulatory frameworks. Additionally, community participation in designing and utilizing IoT solutions is a key factor for successful implementation. By analyzing case studies in several smart cities, this research also provides insights into the challenges faced and strategies employed in integrating IoT into urban management. Based on these findings, the research concludes that a systemic approach encompassing cross-sector collaboration, proven technology use, and active community participation is necessary for successful IoT integration in urban management. This research contributes to expanding the understanding of IoT implementation in a broader urban context and provides practical guidance for policymakers, practitioners, and academics involved in smart city development.